Analisis Variasi Teknik Overlap Data terhadap Citra Anatomi Axial CT-Scan Thorax pada Kasus Tumor Paru - Dwi Sulistyowati; Jeffri Ardiyanto; Budi Prijo Witjaksono (Jurnal Imejing Diagnostik (JImeD), 2017)
Background : The data overlap technique is the distance between the reconstruction images on the Z axis. This technique is useful for reducing the partial effect of volume, where images will be better when post processing is 2D or 3D. The purpose of this research is to know the effect of data overlap technique  variation  on  axial anatomical  image of CT-Scan Thorax  of lung tumor case   and what is  the variation of data overlap technique can yield anatomical image with the best quality.Methods : This research is an quantitative study. Subjects in this study were patients with CT Scan Thorax examination in  cases of lung tumors amounted to 7 people. The results of the scanning that has been done and then recons of data overlap technique using the value of 2 mm, 4 mm, 6 mm and 8 mm then the reconstruction results are assessed by 2 radiologists.Results : it is known that the variation of data overlap significantly affect the quality of the resulting image. For the most optimal data overlap value on CT thorax CT scan with lung tumor case, 2 mm data overlap value has the best result compared to other values with mean rank is 3.99.Conclusion : Based on these results indicate that the variation of data overlap significantly affect the quality of the resulting image. Optimal value of reconstruction increment to see a metastatic pathology is 2 mm.